Politik Gender Dan Keterwakilan Perempuan Dalam Dunia Politik Indonesia: Tinjauan Literatur Sistematis - Astri Tiara Nasti; Nayla Oktaviani; Pramelia Candraningtyas; Wisma Asih Nur Alifiyah; Khoiriya Ulfah (CV. ITTC INDONESIA, 2026)
This study aims to analyze gender politics and women's representation in Indonesian politics through a Systematic Literature Review (SLR) approach. This study focuses on obstacles to women's political representation, the effectiveness of the 30% affirmative action quota policy, patriarchal culture, political education, and the role of political parties in increasing women's political participation. This study uses the Systematic Literature Review (SLR) method by systematically reviewing 20 scientific articles and supporting references published between 2015 and 2025. Data were collected through a process of searching, selecting, evaluating, and synthesizing literature relevant to the theme of gender politics in Indonesia. The analysis was conducted using thematic analysis to identify patterns, obstacles, and strategies for increasing women's representation in politics. The findings indicate that women's representation in Indonesian politics still faces various multidimensional obstacles, including patriarchal culture, gender stereotypes, low political literacy, limited access to economic resources and political networks, and male dominance in political party structures. Although the affirmative action policy in the form of a 30% quota has been implemented, this policy tends to be administrative in nature and has not significantly increased women's substantive representation in the political decision-making process. Furthermore, gender mainstreaming and women's political education have not been optimally implemented by political parties and government institutions. This study emphasizes that increasing women's political participation requires internal efforts within political parties, strengthening gender-based political education, and strengthening the implementation of ongoing affirmative action policies to create a more inclusive and gender-responsive political system. Abstracts are written in English and Indonesian (except articles written in English) which contain the main issues, research